COVID-19 surveillance in Madagascar and Urban Burkina Faso: addressing underreporting of disease burden through integrative analysis of diverse data streams - Rakotozandrindrainy, Njariharinjakamampionona; Kang, Sophie S. Y.; Wandji Nana, Lady R.; Sugimoto, Jonathan D.; Wang, Yi-Ting; Rakotozandrindrainy, Ndrainaharimira; Razafindrabe, Tsiriniaina Jean Luco; Raminosoa, Tiana Mirana; Hong, Sye Lim; Razafindrakalia, Mathilde; Nyirenda, Gabriel; Binger, Tabea; et al. (Clinical infectious diseases, 2025)
Coronavirus disease 2019 (COVID-19) caused substantial disease and death worldwide since December 2019, but the burden was lower in Africa than in high-income countries. To address potential underreporting, we modeled severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and disease burden in Burkina Faso and Madagascar.Prospectively enrolled patients who presented with fever at sentinel healthcare facilities were assessed for active SARS-CoV-2 infection. Household members of SARS-CoV-2-infected patients were prospectively followed for confirmed SARS-CoV-2 infection. Archived serum specimens that spanned the pandemic onset in Madagascar to the start of prospective surveillance were tested for anti-SARS-CoV-2 immunoglobulins. Data from these multiple sources contributed to an integrated analysis to calibrate an epidemiologic mass action model.COVID-19 accounted for a substantial fraction of healthcare-ascertained febrile illness in both Burkina Faso and Madagascar, with symptom profiles consistent with those previously reported. SARS-CoV-2 vaccination coverage was very low in Burkina Faso and unavailable in Madagascar. The household secondary attack rate was 28% (95% confidence intervals [CI], 22%-35%] in Madagascar and 31% (95% CI: 9%-68%) in Burkina Faso, indicating substantial transmission of the disease within households in both locations. Model simulations estimated that the actual number of SARS-CoV-2 infections was at least nine times higher than the reported number of febrile COVID-19 cases.Africa has faced persistent challenges due to underinvestment in vaccination programs and disease surveillance programs. There was substantial underreporting of COVID-19 cases during the pandemic in both countries. Our findings call for improving systems and resources in disease surveillance during epidemic and interepidemic periods in these countries.